Information and society : keynote address to the G7 Ministerial Conference, 25-26 February 1995, Brussels. - GORE, Al Jr. (1995)
Elaborates on the basic principles adopted by the first World Telecommunication Development Conference in 1994, viz. private investment competition; open access; universal service; and, flexible regulations. Points out that these principles have been central to the discussions about the Global Information Infrastructure (GII) in bilateral, multilateral and regional fora, and notes that the challenge is to create the commercial, technical, legal and social conditions that will establish the foundation for the GII.